Campaigning for political rights in Nigeria: the Women Movement in the 1950s - (:unkn) unknown (My University, 2016)
In 1956, the revision of the Nigerian Constitution was seen by the Women Movement of Nigeria (WM) as an opportunity to campaign for the political inclusion of women. The article Allocation system for women, written in 1954 by Mrs Elizabeth Adekogbe, president of the WM, highlights the political rights which these women were claiming, namely universal suffrage and the right to stand for election. These claims however divided the country’s women, who might have different conceptions of their political emancipation depending on their political allegiance. These divisions suggest that we should rethink the umbrella category “women of Nigeria” and rather explore the broad spectrum of women’s political demands, which were largely inspired by Western debates on women’s suffrage. Consequently, the article also allows us to question any parallelism with Western suffragist campaigns and the concept of “citizenship”, as well as its use or non-use by these African women.
Keywords: African Research